2019
DOI: 10.1002/ecs2.2541
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogenic flowering of Aristida beyrichiana following 50 years of fire exclusion

Abstract: Fire-stimulated or pyrogenic flowering is one of many traits that enable plants in fire-prone ecosystems to persist or dominate following frequent fires. Obligate pyrogenic flowering has long been observed in wiregrass (Aristida beyrichiana), a foundation bunchgrass in frequently burned longleaf pine ecosystems in the southeastern United States. Widespread fire exclusion in this ecosystem has contributed to well-documented declines in plant and animal biodiversity prompting the need for restoration efforts. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Quantifying PFF at the community scale is less conducted in savannas than in other regions, and most observations have been made for single, mainly shrub, species (Franceschinelli & Bawa, 2005; Conceição & Orr, 2012; de Sousa & da Cunha, 2018; Dodonov et al, 2018; Shearman et al, 2019, but see Massi et al, 2017; Pilon et al, 2018). In Lamont and Downes’ (2011) review of PFF in Australasia and South Africa, the vast majority of species identified as having this strategy (>70%) were from mediterranean climate regions, whereas only ~14% were from savanna.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantifying PFF at the community scale is less conducted in savannas than in other regions, and most observations have been made for single, mainly shrub, species (Franceschinelli & Bawa, 2005; Conceição & Orr, 2012; de Sousa & da Cunha, 2018; Dodonov et al, 2018; Shearman et al, 2019, but see Massi et al, 2017; Pilon et al, 2018). In Lamont and Downes’ (2011) review of PFF in Australasia and South Africa, the vast majority of species identified as having this strategy (>70%) were from mediterranean climate regions, whereas only ~14% were from savanna.…”
Section: Discussionmentioning
confidence: 99%
“…However, although some observations of this phenomenon were made, studies quantifying the PFF responses in the Cerrado are lacking. Mass PFF events have been documented (Coutinho, 1976;Massi et al 2017;Pilon et al, 2018); however, in general, most studies have focused on the responses of single species rather than at the community level (e.g., Franceschinelli & Bawa, 2005;Conceição & Orr, 2012;Dodonov et al, 2018;Shearman et al, 2019;Sousa and Cunha, 2019). The speed of PFF (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These perennial bunchgrasses are adapted to fire, enabling them to persist and reproduce despite frequently recurring fires ( Platt 1999 , Means 2007 ) as well as to survive for decades without burning ( Shearman et al . 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aristida beyrichiana (wiregrass) is a perennial, endemic C4 bunchgrass that commonly dominates pine savanna understories, contributing to vegetation-fire feedbacks and biodiversity dynamics [ 16 – 18 ]. In savannas where fire has been excluded however, the size and number of wiregrass individuals are greatly reduced [ 19 , 20 ], which could be attributed to competition, lower light levels from overstory shading, or heavy litter [ 21 – 23 ]. Moreover, because sexual reproduction in wiregrass is primarily stimulated by fire, lack of fire inhibits wiregrass seed production [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a stand that had been fire-suppressed for at least 35 years, [ 13 ] found that wiregrass declined after a reintroduction fire and still had not reached pre-burn levels of cover after eight years. In addition, wiregrass’ inflorescence production has been shown to be lower after the reintroduction of fire in long-unburned areas relative to that in frequently burned areas [ 20 ], although it is unknown how this translates to seed viability and germination. None of these studies, however, examined the burning of accumulated fuels as a mechanism by which reintroduction fires affect wiregrass plants.…”
Section: Introductionmentioning
confidence: 99%